Efficacy of Doxycycline plus fixed-dose combination gel of Adapalene and Benzoyl Peroxide versus oral Isotretinoin for the treatment of severe and moderate acne - حبيب, مياسه; رولا بدور ,; جمال خدام, (Latakia University Journal -Medical Sciences Series, 2022)
Background: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous unit. Acne afflicts up to 80% of adolescents and up to 54% of adults. Oral Isotretinoin (ISO) is the gold standard for severe nodular acne. However as some patients are unwilling, unable, or intolerant to ISO, other options are needed. Aim: To compare efficacy and safety of doxycycline plus adapalene 0.1%/benzoyl peroxide 2.5% gel (D+A/BPO) versus oral ISO in severe and moderate acne. Materials and Methods: This study included 112 patients suffering from severe and moderate acne. Doxycycline100mg/d plus adapalene 0.1%/benzoyl peroxide 2.5% gel was applied to both severe and moderate acne patients for 12weeks versus Isotretinoin(0.5mg/kg/d) for 20weeks. The outcomes of the study were assessed using Global Acne Grading System (GAGS) at different time intervals. Results: Patients with moderate acne had significant reduction in acne lesions in both treatment methods (63.86% for (D+A/BPO) vs. 88% for ISO, all p<0.001). Isotretinoin was superior in severe acne treatment (85.11% vs. 25.08% for (D+A/BPO), all p<0.0001) Conclusion: (D+A/BPO) showed significant reduction on GAGS in only moderate acne. Isotretinoin was superior in both severe and moderate acne treatment